ZnFeP-particle gradient abrasion-resistant chemical composite coating and preparation method thereof

By forming a three-layer structure of ZnFeP-particle gradient abrasion-resistant chemical composite coating on the surface of metal components such as electric power tools, the problem of insufficient wear resistance and corrosion resistance in the prior art is solved, and the efficient performance improvement under abrasion conditions is achieved, and the advantages of environmental protection and low cost are provided.

CN119571300APending Publication Date: 2025-03-07ELECTRIC POWER RES INST OF STATE GRID ZHEJIANG ELECTRIC POWER COMAPNY +1

Patent Information

Application Number
CN202411567169.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the wear resistance and corrosion resistance of metal components such as electric power tools under abrasion conditions. The hot-dip galvanized layer is not corrosion-resistant and wear-resistant in high-temperature, high humidity, high chlorine and high wind environments.

Method used

Using ZnFeP-particle gradient anti-absorbing chemical composite plating, a three-layer structure of passivation layer, low-iron ZnFeP-small-particle chemical composite plating and high-iron ZnFeP-large particle chemical composite plating are formed on the surface to form a gradient plating with a corrosion potential from low to high.

Benefits of technology

It significantly improves the wear resistance and corrosion resistance of metal components, ensures service capacity under abrasive conditions, and has the advantages of environmental protection and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571300A_ABST
    Figure CN119571300A_ABST
Patent Text Reader

Abstract

The invention discloses a ZnFeP-particle gradient abrasion-resistant chemical composite coating and a preparation method of the ZnFeP-particle gradient abrasion-resistant chemical composite coating. The ZnFeP-particle gradient abrasion-resistant chemical composite coating is divided into a passivation layer, a low-iron ZnFeP-particle chemical composite coating and a high-iron ZnFeP-particle chemical composite coating from outside to inside, and a gradient coating with the corrosion potential from low to high is formed; the content of iron in the low-iron ZnFeP-particle chemical composite coating ranges from 0.03 wt% to 1.0 wt%, the thickness of the low-iron ZnFeP-particle chemical composite coating ranges from 8 micrometers to 18 micrometers, and the hardness of the low-iron ZnFeP-particle chemical composite coating ranges from 150 HV to 300 HV. The content of iron in the high-iron ZnFeP-particle chemical composite coating ranges from 5 wt% to 30 wt%, the thickness ranges from 8 micrometers to 18 micrometers, and the hardness ranges from 500 HV to 650 HV. By means of the ZnFeP-particle gradient abrasion-resistant chemical composite coating, a metal component can be resistant to abrasion and corrosion, and therefore the service capacity of the metal component such as electric power fittings in the abrasion working condition is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surface treatment, in particular to an environmentally friendly, low-cost ZnFeP-microparticle gradient anti-abrasion chemical composite coating and a preparation method thereof. Background Art

[0002] As the most important basic material, carbon steel is widely used in industries such as electricity, communications, chemicals, automobiles, and national defense. For example, U-shaped rings, ball head hanging rings and other power fittings are exposed to various meteorological conditions all year round, and corrosion occurs all the time. Breeze vibration, dancing, icing, sub-span vibration, wire de-icing and jumping, etc., cause wear of line fittings to varying degrees, which makes power fittings subject to both corrosion and wear. The commonly used hot-dip galvanized layer is neither corrosion-resistant nor wear-resistant in the coastal environment of high temperature, high humidity, high chlorine, and strong winds, resulting in frequent cases of abrasion failure of power fittings. Therefore, the development of an environmentally friendly, low-cost, anti-wear layer with good performance has significant practical significance.

[0003] In order to improve the corrosion resistance of carbon steel and other components, some people have studied zinc alloy coatings such as Zn-Ni, Zn-Co, and Zn-Fe. Among them, the Zn-Fe alloy coating has the lowest cost and is more environmentally friendly. Structure determines performance. Zhang Sifang found that as the Fe content in the Zn-Fe alloy coating gradually increases from less than 0.03wt% to 95wt%, the coating structure also changes from η phase, ζ phase, and γ phase to α phase, which makes the performance of the Zn-Fe alloy layer very different (Zhang Sifang, The influence of Fe content in zinc-iron coating on product coating structure and performance, 2013 National Cold Rolled Strip Production Technology Exchange Conference, 2013: 125-128). When the Fe content is ≤1 wt%, its corrosion resistance can be greatly improved by passivation. For example, Li Xueyuan et al. passivated the Zn-Fe deposited layer with an Fe content of 0.3wt% to 0.9wt%. After 1488 hours of neutral salt spray test, no red rust was observed (Li Xueyuan et al., Study on Electrodeposition and Corrosion Resistance of Zn-Fe Alloy Coating, Acta Aeronautica Sinica, 2000, 21: S58-S61). At this time, Zn-Fe is in η phase (Yang Fangzu et al., Relationship between Iron Content and Properties of Zinc-Fe Alloy Coating, Electroplating and Finishing, 1992, 11 (1): 11-14), and the hardness value is only 120 to 130 HV (Zeng Xiangde, 20 Years of Application Practice of Environmentally Friendly High Corrosion Resistance Zinc-Fe Alloy Electroplating Process, Surface Engineering Information, 2010, 5: 10-13). Obviously, the Zn-Fe alloy layer with Fe content ≤1wt% has good corrosion resistance, but poor tribological properties. When the Fe content is 23 wt%≤≤28 wt%, it presents the γ phase and the hardness value can reach 450~550HV (Zhang Sifang, Influence of Fe content of zinc-iron coating on product coating structure and performance, 2013 National Cold Rolled Strip Production Technology Exchange Conference, 2013: 125-128). However, due to the high iron content, conventional passivation cannot be carried out, which affects its corrosion resistance (Cui Ping et al., Research on electroplating of zinc-iron alloy with low iron content in alkaline solution, Materials Protection, 2008, 41 (9): 31-33, 51). Therefore, the Zn-Fe alloy layer at this time has certain tribological properties, but poor corrosion resistance. In the existing patent literature, the deposition of Zn-Fe alloys with low and high iron contents has been studied. CN104120466A, CN105442000A, CN109137016A, CN1162571C, etc. prepared Zn-Fe alloy coatings with low iron content in acidic or alkaline baths, and CN117535744A and CN101545125A prepared Zn-Fe alloy coatings with iron contents of 12% to 18% and 17% to 20%, respectively. Obviously, a single Zn-Fe alloy coating is difficult to meet the requirements of metal components such as power fittings in abrasive working conditions.

[0004] Composite deposition is an effective technical means to improve the tribological properties of material surfaces. Based on the research on the mechanism of composite deposition, the process is adjusted to significantly improve the wear resistance of the material surface by greatly increasing the content of particles in the coating (HF Zhou, NDu, JK Shang, Characteristics investigation of Ni-diamond compositeelectrodeposition, Electrochimica Acta ., 2015, 151(1): 157-167.), and made use of the organic fusion of the excellent corrosion resistance of Zn-Ni alloy and the strengthening effect of particles to prepare ZnNi-particle anti-wear composite layers with excellent wear resistance (CN104213106B, CN104195533B). CN1854350A, CN1289717C, CN1854351A, etc. used composite electroplating technology to prepare Zn-Fe-SiO2 composite coatings with Fe content of 5wt%-25wt% in an acidic system. The wear resistance is improved compared with that of a single Zn-Fe alloy. The disadvantage is that SiO2 does not have a self-lubricating function and is easy to damage the wear components. In addition, the content of particles in the composite layer is only 0.5%-1%, which has limited effect on improving wear resistance. In addition, there is no related research on the preparation of ZnFeP-particle gradient anti-wear composite layers using chemical composite plating technology. Summary of the invention

[0005] The present invention aims to overcome the defects of the above-mentioned prior art and provide an environmentally friendly and low-cost ZnFeP-microparticle gradient anti-wear chemical composite coating and a preparation method thereof, so as to improve the service capacity of metal components such as power fittings in abrasive conditions.

[0006] To this end, the present invention adopts the following technical solution.

[0007] In the first aspect, the present invention provides a ZnFeP-particle gradient anti-wear chemical composite coating, which is divided into a passivation layer, a low-iron ZnFeP-small particle chemical composite coating and a high-iron ZnFeP-large particle chemical composite coating from the surface to the inside, forming a gradient coating with a corrosion potential from low to high; The low-iron ZnFeP-small particle chemical composite coating has an iron content of 0.03wt%-1.0wt%, a thickness of 8μm-18μm, and a hardness of 150-300HV; The high iron ZnFeP-large particle chemical composite plating layer has an iron content of 5wt%-35wt%, a thickness of 8μm-18μm, and a hardness of 500-650HV.

[0008] Furthermore, the iron content of the low-iron ZnFeP-small particle chemical composite coating is 0.1wt%-1.0wt%, and the iron content of the high-iron ZnFeP-large particle chemical composite coating is 10wt%-30wt%.

[0009] Furthermore, the high iron ZnFeP-large particle chemical composite coating is prepared from the following high iron solution: The high iron solution comprises zinc salt, ammonium ferrous sulfate hexahydrate, first particles, sodium hypophosphite, a multi-component complex system, a combined brightener and a stabilizer; The zinc salt is one of zinc sulfate, zinc acetate, zinc nitrate and zinc chloride, and the concentration is 0.1-0.3 mol / L; The concentration of the ammonium ferrous sulfate hexahydrate is 18-40 g / L; The first particles are a mixture of 45 nanometer-10 micrometer particles and 15-30 micrometer particles; the concentration of the 45 nanometer-10 micrometer particles is 5-50 g / L, and the concentration of the 15-30 micrometer particles is 50-150 g / L; The concentration of sodium hypophosphite is 10-30 g / L; The multi-component complex system is an acidic system, which is a mixture of EDTA or its sodium salt, DTPA or its sodium salt, citric acid, and sodium gluconate; the concentration of EDTA or its sodium salt is 10-25 g / L, the concentration of DTPA or its sodium salt is 0-10 g / L, the concentration of citric acid is 15-30 g / L, and the concentration of sodium gluconate is 10-30 g / L.

[0010] This multi-component complex system is an acidic system, which is more likely to adsorb cations; this multi-component complex system and Fe 2+ Complexing ability is better than Zn 2+ Weak, resulting in a higher concentration of free Fe in the solution 2+ , thereby forming a high iron solution. The first particles are composed of particles of two different particle sizes.

[0011] Furthermore, the concentration of the ammonium ferrous sulfate hexahydrate is 18-30 g / L; the first particles are a mixture of 100 nanometers-5 micrometers self-lubricating particles and 20-25 micrometers self-lubricating particles, the concentration of 100 nanometers-5 micrometers self-lubricating particles is 20-40 g / L, and the concentration of 20-25 micrometers self-lubricating particles is 80-120 g / L; the concentration of the sodium hypophosphite is 15-26 g / L; in the multi-component complex system, the concentration of citric acid is 18-25 g / L, and the concentration of sodium gluconate is 15-20 g / L.

[0012] Furthermore, the high iron solution also includes other additives, and the other additives are a mixture of one or more of tetrahydrothiazolidinethione, boric acid, rare earth salts, and surfactants; the concentration of the tetrahydrothiazolidinethione is 0-20 mg / L (preferably, 0-5 mg / L for carbon steel and copper substrates, and 10-20 mg / L for aluminum substrates); the concentration of boric acid is 20-30 g / L; the rare earth salt is one or more of nitrates, acetates, sulfates and chlorides containing rare earth elements, and the concentration is 0.001-0.025 mol / L; the surfactant is a mixture of one or more of chlorhexidine, quaternary ammonium salt surfactants and pyridine surfactants, and the concentration is 0.04-0.8 g / L.

[0013] Furthermore, the low-iron ZnFeP-small particle chemical composite coating is prepared from the following low-iron solution: The solution comprises zinc oxide, sodium hydroxide, ammonium ferrous sulfate hexahydrate, second particles, sodium hypophosphite, a multi-component complex system, a combined brightener and a stabilizer; The concentration of the zinc oxide is 20-40 g / L; The concentration of the sodium hydroxide is 50-120 g / L; The concentration of the ammonium ferrous sulfate hexahydrate is 1.5-15 g / L; The particle size of the second microparticles is 10 nanometers to 15 micrometers, and the concentration is 30-150 g / L; The concentration of the sodium hypophosphite is 15-35 g / L; The multi-component complex system is an alkaline system, which is a mixture of sodium salicylate, sodium citrate or ammonium citrate, pyridine and triethanolamine. The concentration of sodium salicylate is 3-18 g / L, the concentration of sodium citrate or ammonium citrate is 10-30 g / L, the concentration of pyridine is 0-18 g / L, and the concentration of triethanolamine is 5-20 mL / L.

[0014] This multi-component complex system and Fe 2+ Complexing ability is better than Zn 2+ Strong, making the free Fe in the solution 2+ The content is low, resulting in a low iron solution.

[0015] Furthermore, the concentration of the ammonium ferrous sulfate hexahydrate is 2-8 g / L; the second particles are self-lubricating particles with a particle size of 45 nanometers to 10 microns and a concentration of 50-100 g / L; the concentration of the sodium hypophosphite is 20-30 g / L; in the multi-component complex system, the concentration of sodium salicylate is 5-12 g / L, the concentration of sodium citrate or ammonium citrate is 12-25 g / L, the concentration of pyridine is 0-12 g / L, and the concentration of triethanolamine is 10-15 mL / L.

[0016] Furthermore, the low-iron solution also includes other additives, and the other additives are one or two of rare earth salts and surfactants; the rare earth salts are one or more of nitrates, acetates, sulfates and chlorides of rare earth elements, taking 0.001-0.025 mol / L; the surfactants are one or two of chlorhexidine and quaternary ammonium salt surfactants, with a concentration of 0.04-0.8 g / L.

[0017] Furthermore, the combined brightener in the high-iron solution and the low-iron solution is a mixture of benzylpyridinium carboxylate and one or more of vanillin, piperonal, heliotropin, polyethylene glycol, and butynediol; the concentration of benzylpyridinium carboxylate is 0.05-0.2 mL / L (preferably 0.06-0.12 mL / L), the concentration of the mixture of one or more of vanillin, piperonal, and heliotropin is 50-150 mg / L (preferably 60-100 mg / L), and the concentration of the mixture of one or two of polyethylene glycol and butynediol is 40-120 mg / L (preferably 50-80 mg / L).

[0018] Furthermore, the stabilizer in the high iron solution is a mixture of one or more of potassium sodium tartrate, ascorbic acid, sodium bisulfite, and manganese dichloride; the concentration of potassium sodium tartrate is 8-20 g / L (preferably 10-15 g / L), the concentration of ascorbic acid is 1.5-5 g / L (preferably 1.8-3 g / L), the concentration of sodium bisulfite is 10-150 mg / L (preferably 20-90 mg / L), and the concentration of manganese dichloride is 0-5 g / L (preferably 0-3 g / L).

[0019] Furthermore, the stabilizer in the low-iron solution is a mixture of one or more of potassium sodium tartrate, sodium ascorbate, sodium sulfite, and manganese dichloride; the concentration of potassium sodium tartrate is 8-20 g / L (preferably 10-15 g / L), the concentration of sodium ascorbate is 0.5-3 g / L (preferably 0.8-2 g / L), the concentration of sodium sulfite is 5-20 mg / L (preferably 8-12 mg / L), and the concentration of manganese dichloride is 0-5 g / L (preferably 0-3 g / L).

[0020] The high-iron solution is an acidic system, and the stabilizer is mainly acidic substances, such as ascorbic acid, sodium bisulfite, etc.; the low-iron solution is an alkaline system, and the stabilizer is mainly sodium ascorbate and sodium sulfite.

[0021] Furthermore, the passivation layer is prepared from a solution consisting of chromium nitrate nonahydrate, sodium nitrate, sodium oxalate, sodium malonate, maleic anhydride, cobalt nitrate hexahydrate and amino silicon: the concentration of the chromium nitrate nonahydrate is 40-80 g / L; the concentration of the sodium nitrate is 5-20 g / L; the concentration of the sodium oxalate is 10-20 g / L; the concentration of the sodium malonate is 10-20 g / L; the concentration of the maleic anhydride is 1-2 g / L; the concentration of the cobalt nitrate hexahydrate is 5-8 g / L; and the concentration of the amino silicon is 3-5 mL / L.

[0022] Further, the first particles or the second particles are selected from one or a mixture of several of diamond particles, silicon carbide particles, silicon dioxide particles, boron nitride particles, aluminum oxide particles, molybdenum sulfide particles, zirconium dioxide particles, titanium dioxide particles, silicon nitride particles, tungsten carbide particles, polytetrafluoroethylene particles, carbon fiber particles, carbon nanotube particles, graphite particles, carbon nanotubes and graphene particles, preferably a mixture of one or more of self-lubricating particles such as hexagonal boron nitride particles, aluminum oxide particles, polytetrafluoroethylene particles, molybdenum sulfide particles, graphite particles, carbon nanotubes, graphene particles, etc.

[0023] In a second aspect, the present invention provides a method for preparing the above-mentioned ZnFeP-microparticle gradient anti-wear chemical composite coating, the steps of which are as follows: firstly, the metal component is subjected to a pretreatment of degreasing-water washing-rust removal-water washing-activation, and after water washing, it is immersed in a high-iron solution for composite deposition, and intermittent stirring is adopted at the same time, and the stirring intensity is preferably such that large microparticles are not easy to settle, and is specifically adjusted according to the size of the tank body, the particle size and density, etc., to obtain a metal component covered with a high-iron ZnFeP-large microparticle chemical composite coating; after water washing, it is immersed in a low-iron solution for composite deposition, and intermittent stirring is adopted at the same time, so that the high-iron ZnFeP-large microparticle chemical composite coating is covered with a low-iron ZnFeP-small microparticle chemical composite coating, and after water washing, it is subjected to light exposure-water washing-passivation-water washing-sealing-drying, so that the low-iron ZnFeP-small microparticle chemical composite coating is covered with a passivation layer, thereby obtaining the desired ZnFeP-microparticle gradient anti-wear chemical composite coating on the surface of the metal component; The temperature of deposition in high iron solution is 40-80°C, and the time is 20-40 minutes; the temperature of deposition in low iron solution is 40-80°C, and the time is 30-60 minutes; during passivation treatment, nitric acid or sodium hydroxide is used to adjust the pH value of the solution to 2.0-2.5, the temperature is 20-45°C, and the time is 30-60s.

[0024] The above-mentioned degreasing, rust removal and activation are aimed at obtaining a fresh substrate surface. Conventional treatment processes are sufficient. A 0.2-0.5% dilute nitric acid solution can be used for polishing, and trivalent chromium passivation or chromium-free passivation can be used for passivation.

[0025] The beneficial effects of the present invention are as follows: 1. The corrosion resistance of the three-layer structure of "passivation layer---low iron ZnFeP-small particle chemical composite coating---high iron ZnFeP-large particle chemical composite coating" is guaranteed from four aspects. First, the passivation of the outer layer of low Fe content ZnFeP-small particle composite coating is used to form a passivation film, laying the foundation for good corrosion resistance. Secondly, the potential difference between the coating and the steel substrate is gradually shortened by the gradient of increasing Fe content from the surface to the inside, so that it still has a certain corrosion resistance after the outer layer is gradually consumed. Thirdly, the ZnFeP alloy layer acts as a sacrificial anode to provide cathodic protection for carbon steel and copper substrates. Finally, the cathodic polarization of the rare earth salts and particles in the additives makes the deposited layer denser.

[0026] 2. Improve the tribological properties of the three-layer structure from three aspects. First, the Fe content gradient from the surface to the inside forms a passivation layer and a structural gradient from the η phase to the γ phase in the metal component, thereby forming a hardness gradient of the three-layer structure: from 150 to 300 HV of the ZnFeP-particle composite coating when the outer layer has a low Fe content to 500 to 650 HV of the ZnFeP-particle composite coating when the inner layer has a high Fe content. Secondly, the hardness of the anti-wear composite layer is further improved through the dispersion strengthening effect of the particles and the fine grain strengthening effect of the rare earth ions (rare earth ions are easily adsorbed on the surface of the electrode and the particles, thereby increasing the polarization resistance of the deposition system and promoting grain refinement). Finally, the self-lubricating particles are used to greatly reduce the friction coefficient of the anti-wear composite layer, and the effect is enhanced by the mutual matching of the inner layer large-size particles and the outer layer small-size particles.

[0027] 3. Increase the content of particles in the composite layer from three aspects. First, use intermittent stirring. The interfacial force between the newly formed metal and the particles during composite deposition is conducive to the retention of particles on the metal surface. Intermittent stirring can make full use of the retention effect of the interfacial force, thereby significantly increasing the content of particles in the composite layer. Second, add rare earth ions. Rare earth ions are easily adsorbed on the surface of metals and particles, which not only promotes grain refinement, but also allows particles to absorb more positive charges, promote the movement and retention of particles to the metal surface, thereby increasing the composite amount. Third, the adsorption of cationic surfactants on the surface of particles increases the Zeta potential of particles, thereby promoting the dispersion, transmission and retention of particles.

[0028] 4. Using the difference in complexing ability and Fe 2+ The concentration difference of Fe is used to adjust the iron content in the deposited layer. 2+ Weak complexation, with Zn 2+ Strong complexing system (such as EDTA or its sodium salt, DTPA or its sodium salt, etc.), while using high Fe 2+ concentration (to achieve this by controlling the concentration of ammonium ferrous sulfate hexahydrate); when preparing the lower ZnFeP-small particle composite layer, the Fe 2+Strong complexation with Zn 2+ Weakly complexed complex systems (such as sodium salicylate, sodium citrate or ammonium citrate, etc.), while using low Fe 2+ concentration (achieved by controlling the concentration of ammonium ferrous sulfate hexahydrate).

[0029] 5. Use the antioxidant effects of ascorbic acid, sodium sulfite (sodium bisulfite in acidic system), manganese dichloride, etc., and the complex system to Fe 2+ The complexation effect inhibits the Fe 2+ oxidation; use potassium sodium tartrate to mask impurity ions; rare earth ions can be adsorbed on the surface of aluminum, hindering Al 3+ It can enter the plating solution to produce poisoning effects, and can also form stable rare earth citrate anions with the complexing agent citrate to reduce the generation of precipitated impurities. 3+ The strong complexation is also beneficial to improve the stability of the chemical plating solution.

[0030] 6. Environmental advantages. Compared with hot-dip galvanizing, the ZnFeP-microparticle chemical composite plating process at 40-80°C replaces the current hot-dip galvanizing process at about 450°C, which has obvious advantages of low carbon and low energy consumption; compared with ZnNi electrodeposition and ZnNiP chemical plating, Fe 2+ Replace Ni 2+ , with good environmental properties.

[0031] 7. Low cost advantage. Zn in low iron solution and high iron solution 2+ with Fe 2+ Widely available and inexpensive. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions in the embodiments or technologies of the present invention, the drawings used in the embodiments or technical descriptions are briefly introduced below.

[0033] Figure 1 This is a schematic diagram of the structure of the microparticle gradient anti-abrasion chemical composite coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention.

[0035] Example 1 A 10×20×2 mm Q235 test piece was polished with #2000 sandpaper, washed with deionized water, and then subjected to pretreatments such as degreasing-washing-rust removal-washing-activation. After washing, it was immersed in a high iron solution.

[0036] The composition of the high iron solution is: 18g / L zinc sulfate, 30g / L ammonium ferrous sulfate hexahydrate, 24g / L sodium hypophosphite, 15g / L EDTA, 25g / L citric acid, 20g / L sodium gluconate in the multi-component complex system, 40g / L hexagonal boron nitride with a particle size of 3 microns and 120g / L hexagonal boron nitride with a particle size of 20 microns as the first particle, 0.1mL / L benzylpyridinium carboxylate, 80mg / L vanillin, 60mg / L polyethylene glycol in the combined brightener, 15g / L potassium sodium tartrate, 2.5g / L ascorbic acid, 50mg / L sodium bisulfite in the stabilizer, 20g / L boric acid, 3g / L cerium sulfate, and 0.2g / L chlorhexidine in other additives. An intermittent stirring method with mechanical stirring was adopted, with a stirring intensity of 500 rpm, stirring for 20 seconds and stopping for 10 seconds, and a water bath temperature of 65°C. After 30 minutes, a bright and smooth ZnFeP-large particle chemical composite coating was obtained on the surface of the Q235 test piece.

[0037] The EDS semi-quantitative analysis of the coating without particles showed that the zinc content of the composite coating was 71.4wt.%, the iron content was 22.7wt.%, the phosphorus content was 1.8wt.%, and the balance was other. The composite coating was corroded with sulfuric acid, and the particle content was 15.6v%. The hardness value tested by the microhardness tester was 571HV.

[0038] The Q235 test piece coated with high-iron ZnFeP-large particle chemical composite coating was immersed in a low-iron solution for deposition.

[0039] The composition of the low-iron solution is: 20g / L zinc oxide, 100g / L sodium hydroxide, 4g / L ammonium ferrous sulfate hexahydrate, 18g / L sodium hypophosphite, 100g / L hexagonal boron nitride with a particle size of 3 microns as the second particle, 10mL / L triethanolamine, 18g / L sodium salicylate, 15g / L sodium citrate in the multi-component complex system, 0.1mL / L benzylpyridinium carboxylate, 70mg / L vanillin, 60mg / L butynediol in the combined brightener, 12g / L potassium sodium tartrate, 1g / L sodium ascorbate, 8mg / L sodium sulfite as the stabilizer, 0.5g / L ceric sulfate, 0.5g / L chlorhexidine in other additives. Adopt mechanical stirring intermittent stirring mode, stirring intensity 400rpm, stirring 20s, stop 20s, water bath temperature 70℃, after 45 minutes, low iron ZnFeP-small particle chemical composite coating is obtained on the surface of Q235 test piece covered with high iron ZnFeP-large particle chemical composite coating. EDS semi-quantitative analysis of the surface low iron coating without particles shows that the zinc content in the obtained composite coating is 94.4wt.%, the iron content is 0.7wt.%, the phosphorus content is 0.9wt.%, and the balance is others. The composite coating is corroded by sulfuric acid, and the particle content is 11.5v%. The hardness value tested by microhardness tester is 176HV.

[0040] The test piece obtained by the above process is subjected to post-treatment steps such as light-washing-passivation-washing-sealing-drying to obtain the required particle gradient anti-wear chemical composite coating. The passivation process is: 60g / L chromium nitrate nonahydrate, 15g / L sodium nitrate, 10g / L sodium oxalate, 10g / L sodium malonate, 2g / L maleic anhydride, 6g / L cobalt nitrate hexahydrate, 4mL / L amino silicon. The pH value is adjusted to 2 with nitric acid or sodium hydroxide, the temperature is 30℃, and the time is 25s.

[0041] Figure 1 This is a schematic diagram of the three-layer anti-corrosion structure of "passivation layer-low iron ZnFeP-small particle chemical composite coating-high iron ZnFeP-large particle chemical composite coating" prepared in the embodiment of the present invention. Figure 1 It can be seen that with the increase of iron content from the surface to the inside, the potential difference between the anti-wear layer and the carbon steel substrate gradually shortens, thereby maintaining good corrosion resistance under the joint action of the passivation layer. At the same time, the hardness value increases significantly with the evolution of the outer layer η phase to the inner layer γ phase. Combined with the tribological properties of the self-lubricating particles, the anti-wear layer is endowed with good wear resistance.

[0042] Comparative Example 1 (without passivation treatment) A 10×20×2 mm Q235 test piece was polished with #2000 sandpaper, washed with deionized water, and then subjected to pretreatments such as degreasing-washing-rust removal-washing-activation. After washing, it was immersed in a high iron solution.

[0043] The composition of the high iron solution is: 18g / L zinc sulfate, 30g / L ammonium ferrous sulfate hexahydrate, 24g / L sodium hypophosphite, 15g / L EDTA, 25g / L citric acid, 20g / L sodium gluconate in the multi-component complex system, 40g / L hexagonal boron nitride with a particle size of 3 microns and 120g / L hexagonal boron nitride with a particle size of 20 microns as the first particle, 0.1mL / L benzylpyridinium carboxylate, 80mg / L vanillin, 60mg / L polyethylene glycol in the combined brightener, 15g / L potassium sodium tartrate, 2.5g / L ascorbic acid, 50mg / L sodium bisulfite in the stabilizer, 20g / L boric acid, 3g / L cerium sulfate, and 0.2g / L chlorhexidine in other additives. An intermittent stirring method with mechanical stirring was adopted, with a stirring intensity of 500 rpm, stirring for 20 seconds and stopping for 10 seconds, and a water bath temperature of 65°C. After 30 minutes, a bright and smooth ZnFeP-large particle chemical composite coating was obtained on the surface of the Q235 test piece.

[0044] The Q235 test piece coated with high-iron ZnFeP-large particle chemical composite coating was immersed in a low-iron solution for deposition.

[0045] The composition of the low-iron solution is: 20g / L zinc oxide, 100g / L sodium hydroxide, 4g / L ammonium ferrous sulfate hexahydrate, 18g / L sodium hypophosphite, 100g / L hexagonal boron nitride with a particle size of 3 microns as the second particle, 10mL / L triethanolamine, 18g / L sodium salicylate, 15g / L sodium citrate in the multi-component complex system, 0.1mL / L benzylpyridinium carboxylate, 70mg / L vanillin, 60mg / L butynediol in the combined brightener, 12g / L potassium sodium tartrate, 1g / L sodium ascorbate, 8mg / L sodium sulfite as the stabilizer, 0.5g / L ceric sulfate, 0.5g / L chlorhexidine in other additives. An intermittent stirring method with mechanical stirring was adopted, with a stirring intensity of 400 rpm, stirring for 20 s and stopping for 20 s, and a water bath temperature of 70°C. After 45 minutes, a low-iron ZnFeP-small-particle chemical composite coating was obtained on the surface of the Q235 test piece covered with a high-iron ZnFeP-large-particle chemical composite coating.

[0046] The sample of Example 1 and the sample of Comparative Example 1 were subjected to a 1000-hour neutral salt spray test. No red rust was observed on the sample of Example 1, but red rust was observed on the sample of Comparative Example 1.

[0047] Comparative Example 2 (without low iron solution deposition and passivation treatment) A 10×20×2 mm Q235 test piece was polished with #2000 sandpaper, washed with deionized water, and then subjected to pretreatments such as degreasing-washing-rust removal-washing-activation. After washing, it was immersed in a high-iron solution without particles.

[0048] The composition of the high iron solution is: zinc sulfate 18g / L, ammonium ferrous sulfate hexahydrate 30g / L, sodium hypophosphite concentration 24g / L, EDTA 15g / L, citric acid 25g / L, sodium gluconate 20g / L in the multi-component complex system, benzyl pyridinium carboxylate 0.1mL / L, vanillin 80mg / L, polyethylene glycol 60mg / L in the combined brightener, potassium sodium tartrate 15g / L, ascorbic acid 2.5g / L, sodium bisulfite 50mg / L in the stabilizer, boric acid 20g / L, cerium sulfate 3g / L, chlorhexidine 0.2g / L in other additives. The intermittent stirring mode of mechanical stirring is adopted, the stirring intensity is 500rpm, stirring for 20s, stopping for 10s, the water bath temperature is 65℃, and after 30 minutes, the surface of the Q235 test piece obtains a bright and smooth ZnFeP chemical plating layer.

[0049] The hardness value of the microhardness tester is 452HV. Compared with the high iron layer 571HV in Example 1, it can be found that the dispersion strengthening effect of the particles can improve the hardness of the coating. Obviously, since the selected particles are self-lubricating particles, the reduction of the friction coefficient also gives the material excellent tribological properties.

[0050] Example 2 A 10×20×2 mm 5052 aluminum specimen was polished with #2000 sandpaper, washed with deionized water, and then subjected to pretreatments such as degreasing-washing-rust removal-washing-activation. After washing, it was immersed in a high-iron solution for deposition.

[0051] The composition of the high iron solution is: 18g / L zinc sulfate, 30g / L ammonium ferrous sulfate hexahydrate, 24g / L sodium hypophosphite, 15g / L EDTA, 25g / L citric acid, 20g / L sodium gluconate in the multi-component complex system, 40g / L hexagonal boron nitride with a particle size of 3 microns, 120g / L hexagonal boron nitride with a particle size of 20 microns as the first particle, 0.1mL / L benzylpyridinium carboxylate, 80mg / L vanillin, 60mg / L polyethylene glycol in the combined brightener, 15g / L potassium sodium tartrate, 2.5g / L ascorbic acid, 50mg / L sodium bisulfite in the stabilizer, 15mg / L tetrahydrothiazolidinethione, 20g / L boric acid, 3g / L cerium sulfate, 0.2g / L chlorhexidine in other additives. The intermittent stirring intensity was 500 rpm, stirring for 20 seconds and stopping for 10 seconds, the water bath temperature was 65°C, and after 30 minutes, a bright and smooth ZnFeP-large particle chemical composite coating was obtained on the surface of the 5052 aluminum test piece.

[0052] The results of EDS semi-quantitative analysis showed that the zinc content in the obtained coating was 78.3wt.%, the iron content was 18.3wt.%, the phosphorus content was 1.9wt.%, and the remainder was others.

[0053] The EDS semi-quantitative analysis of the coating without particles showed that the zinc content of the composite coating was 72.6wt.%, the iron content was 24.6wt.%, the phosphorus content was 1.4wt.%, and the balance was other. The composite coating was corroded with sulfuric acid, and the particle content was 13.2v%. The hardness value tested by the microhardness tester was 511HV.

[0054] The 5052 aluminum test piece coated with the ZnFeP-large particle chemical composite coating was immersed in a low iron solution for deposition. The composition of the low iron solution and the subsequent treatment method were the same as those in Example 1.

[0055] It is obvious that those skilled in the art can easily make various modifications to the above embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art to the present invention based on the disclosure of the present invention should be within the protection scope of the present invention.

Claims

1. A ZnFeP-particle gradient anti-wear chemical composite coating, characterized in that: From the surface to the inside, it is divided into a passivation layer, a low-iron ZnFeP-small particle chemical composite coating and a high-iron ZnFeP-large particle chemical composite coating, forming a gradient coating with corrosion potential from low to high; The low-iron ZnFeP-small particle chemical composite coating has an iron content of 0.03wt%-1.0wt%, a thickness of 8μm-18μm, and a hardness of 150-300HV; The high iron ZnFeP-large particle chemical composite plating layer has an iron content of 5wt%-35wt%, a thickness of 8μm-18μm, and a hardness of 500-650HV.

2. The ZnFeP-particle gradient anti-wear chemical composite coating according to claim 1, characterized in that: The iron content of the low-iron ZnFeP-small particle chemical composite coating is 0.1wt%-1.0wt%, and the iron content of the high-iron ZnFeP-large particle chemical composite coating is 10wt%-30wt%.

3. The ZnFeP-particle gradient anti-wear chemical composite coating according to claim 1 or 2, characterized in that: The high iron ZnFeP-large particle chemical composite coating is prepared from the following high iron solution: The high iron solution comprises zinc salt, ammonium ferrous sulfate hexahydrate, first particles, sodium hypophosphite, a multi-component complex system, a combined brightener and a stabilizer; The zinc salt is one of zinc sulfate, zinc acetate, zinc nitrate and zinc chloride, and the concentration is 0.1-0.3 mol / L; The concentration of the ammonium ferrous sulfate hexahydrate is 18-40 g / L; The first particles are a mixture of particles of two sizes: 45 nanometers to 10 micrometers and 15 to 30 micrometers; the concentration of the 45 nanometers to 10 micrometers particles is 5 to 50 g / L, and the concentration of the 15 to 30 micrometers particles is 50 to 150 g / L; The concentration of sodium hypophosphite is 10-30 g / L; The multi-component complex system is an acidic system, which is a mixture of EDTA or its sodium salt, DTPA or its sodium salt, citric acid, and sodium gluconate; the concentration of EDTA or its sodium salt is 10-25 g / L, the concentration of DTPA or its sodium salt is 0-10 g / L, the concentration of citric acid is 15-30 g / L, and the concentration of sodium gluconate is 10-30 g / L.

4. The ZnFeP-particle gradient anti-wear chemical composite coating according to claim 3, characterized in that: The concentration of the ammonium ferrous sulfate hexahydrate is 18-30 g / L; the first particles are a mixture of 100 nanometers to 5 micrometers self-lubricating particles and 20-25 micrometers self-lubricating particles, the concentration of the 100 nanometers to 5 micrometers self-lubricating particles is 20-40 g / L, and the concentration of the 20-25 micrometers self-lubricating particles is 80-120 g / L; the concentration of the sodium hypophosphite is 15-26 g / L; in the multi-component complex system, the concentration of citric acid is 18-25 g / L, and the concentration of sodium gluconate is 15-20 g / L.

5. The ZnFeP-particle gradient anti-wear chemical composite coating according to claim 3, characterized in that: The high iron solution also includes other additives, which are a mixture of one or more of tetrahydrothiazolidinethione, boric acid, rare earth salts, and surfactants; the concentration of tetrahydrothiazolidinethione is 0-20 mg / L; the concentration of boric acid is 20-30 g / L; the rare earth salt is one or more of nitrates, acetates, sulfates, and chlorides containing rare earth elements, with a concentration of 0.001-0.025 mol / L; the surfactant is a mixture of one or more of chlorhexidine, quaternary ammonium salt surfactants, and pyridine surfactants, with a concentration of 0.04-0.8 g / L.

6. The ZnFeP-particle gradient anti-wear chemical composite coating according to claim 3, characterized in that: The low-iron ZnFeP-small particle chemical composite coating is prepared from the following low-iron solution: The solution comprises zinc oxide, sodium hydroxide, ammonium ferrous sulfate hexahydrate, second particles, sodium hypophosphite, a multi-component complex system, a combined brightener and a stabilizer; The concentration of the zinc oxide is 20-40 g / L; The concentration of the sodium hydroxide is 50-120 g / L; The concentration of the ammonium ferrous sulfate hexahydrate is 1.5-15 g / L; The particle size of the second microparticles is 10 nanometers to 15 micrometers, and the concentration is 30-150 g / L; The concentration of the sodium hypophosphite is 15-35 g / L; The multi-component complex system is an alkaline system, which is a mixture of sodium salicylate, sodium citrate or ammonium citrate, pyridine and triethanolamine. The concentration of sodium salicylate is 3-18 g / L, the concentration of sodium citrate or ammonium citrate is 10-30 g / L, the concentration of pyridine is 0-18 g / L, and the concentration of triethanolamine is 5-20 mL / L.

7. The ZnFeP-particle gradient anti-wear chemical composite coating according to claim 6, characterized in that: The concentration of the ammonium ferrous sulfate hexahydrate is 2-8 g / L; the second particles are self-lubricating particles with a particle size of 45 nanometers to 10 microns and a concentration of 50-100 g / L; the concentration of the sodium hypophosphite is 20-30 g / L; in the multi-component complex system, the concentration of sodium salicylate is 5-12 g / L, the concentration of sodium citrate or ammonium citrate is 12-25 g / L, the concentration of pyridine is 0-12 g / L, and the concentration of triethanolamine is 10-15 mL / L.

8. The ZnFeP-particle gradient anti-wear chemical composite coating according to claim 6, characterized in that: The low-iron solution also includes other additives, which are one or two of rare earth salts and surfactants; the rare earth salts are one or more of nitrates, acetates, sulfates and chlorides of rare earth elements, taking 0.001-0.025 mol / L, and the surfactants are one or two of chlorhexidine and quaternary ammonium salt surfactants, with a concentration of 0.04-0.8 g / L.

9. The ZnFeP-particle gradient anti-wear chemical composite coating according to claim 1, characterized in that: The passivation layer is prepared from a solution consisting of chromium nitrate nonahydrate, sodium nitrate, sodium oxalate, sodium malonate, maleic anhydride, cobalt nitrate hexahydrate and amino silicon: the concentration of the chromium nitrate nonahydrate is 40-80 g / L; the concentration of the sodium nitrate is 5-20 g / L; the concentration of the sodium oxalate is 10-20 g / L; the concentration of the sodium malonate is 10-20 g / L; the concentration of the maleic anhydride is 1-2 g / L; the concentration of the cobalt nitrate hexahydrate is 5-8 g / L; and the concentration of the amino silicon is 3-5 mL / L.

10. The method for preparing the ZnFeP-microparticle gradient anti-wear chemical composite coating according to any one of claims 6 to 8, characterized in that: First, the metal component is subjected to a pretreatment of degreasing-washing-rust removal-washing-activation, and then immersed in a high-iron solution for composite deposition after washing, and intermittent stirring is adopted at the same time, and the stirring intensity is preferably such that large particles do not settle, and is specifically adjusted according to the size of the tank body, the particle size and the density of the particles, so as to obtain a metal component covered with a high-iron ZnFeP-large particle chemical composite plating layer; after washing, the metal component is immersed in a low-iron solution for composite deposition, and intermittent stirring is adopted at the same time, so that the high-iron ZnFeP-large particle chemical composite plating layer is covered with a low-iron ZnFeP-small particle chemical composite plating layer; after washing, the metal component is subjected to light exposure-washing-passivation-washing-sealing-drying, so that the low-iron ZnFeP-small particle chemical composite plating layer is covered with a passivation layer, thereby obtaining a desired ZnFeP-particle gradient anti-wear chemical composite plating layer on the surface of the metal component; The temperature of deposition in high iron solution is 40-80°C, and the time is 20-40 minutes; the temperature of deposition in low iron solution is 40-80°C, and the time is 30-60 minutes; during passivation treatment, nitric acid or sodium hydroxide is used to adjust the pH value of the solution to 2.0-2.5, the temperature is 20-45°C, and the time is 30-60s.

Citation Information

Patent Citations

  • Bright corrosion resisting zinc-iron alloy plating process

    CN101545125A

  • Weak acid chloride electroplating solution used for neodymium iron boron electroplating of zinc-iron alloy and preparation method

    CN104120466A

  • A kind of nickel zinc phosphorus chemical plating and its preparation method and chemical plating solution

    CN104195533B

  • A nickel-zinc-phosphorus microparticle composite chemical plating layer and its preparation method

    CN104213106B

  • Alkaline zinc-iron alloy electroplate liquid, preparation method and electroplating process

    CN105442000A

Cited By

  • Abrasion-resistant composite layer and preparation method thereof

    CN119900060A

  • An anti-abrasion composite layer and its preparation method

    CN119900060B

  • Gradient carbon-nitrogen-zinc-iron corrosion-resistant composite layer, preparation method thereof and connection fitting

    CN120041899A

  • Gradient carbon-nitrogen-zinc-iron corrosion-resistant composite layer, its preparation method, and connecting fitting

    CN120041899B